Direct Consultation and Virtual Consultation in the framework for Management BUMDES for Optimization of Financial in Sekaran, Loceret, Nganjuk, East Java - Eko Wahyudi; Anajeng Esri Edhi Mahanani; Rohmatul Faizah (Future Science)
Based on research by socio-legal that is to see the implementation of BUMDES management directly in Desa Sekaran, Loceret, Nganjuk, it was concluded that the existence of BUMDES Sekaran, Loceret, Nganjuk is still at the initial development level because it is still at the level of activity and business program design. This condition encourages the need for BUMDES to be developed at the level of management, financial management, as well as a basic understanding of the law. Higher Education, in this case, has an important role considering the dharma of community service is also attached to it. Besides, although the village has a village assistant, its existence as a village facilitator has not been able to answer the problem, the facilitator has not been able to provide knowledge of financial management and BUMDES optimally. Based on the results of field research through direct interviews with the Sekaran Head, and the BUMDES Chairperson, solutions were then drawn to provide financial management and BUMDES assistance, as well as legal understanding through direct consultation and virtual consultation. Direct consultations are held at the forum, while virtual consultations show sustainability.